Inflammatory Periimplant Diseases and the Periodontal Connection Question - Passariello, Claudio; Di Nardo, Dario; Testarelli, Luca (European Journal of Dentistry, 2019)
Implant therapy has become a widespread reality in modern dentistry. Nevertheless, dental implants can fail due to different causes, among which inflammatory peri-implant diseases (IPDs) are a major challenge, with prevalences that are much higher than previously believed.Specific searches were undertaken for each question raised between October and November 2017, in the PubMed website database (US National Library of Medicine, National Institutes of Health; Bethesda, Maryland, United States). Only articles written in English and published from 2007 onward were considered initially. The following keywords were used in the searches “periimplantitis (PI),” “periimplant mucositis (PM),” “dental implant failure,” “periimplant microbiota,” “periodontal microbiota,” “implant failure” (no temporal limit), and “foreign body reaction” (no temporal limit). The selection process resulted in the selection of 239 articles that were analyzed in detail in elaborating this review. The reference list was limited to the 47 most relevant articles due to editorial limits of this Journal.Intrinsic differences between natural teeth and dental implants are able to give rise to inflammatory diseases that share only minor and scarcely relevant characters, and would consequently deserve different and specifically designed instruments and strategies, for both diagnosis and therapy.
Keywords: gingivitis; pathogenesis; periimplant mucositis; periimplantitis; periodontitis